2020
DOI: 10.21203/rs.3.rs-50761/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dysregulation of the Hypothalamic-pituitary-adrenal Axis in Diet-induced Prediabetic Male Sprague Dawley Rats

Abstract: Background: Altered function of the hypothalamic-pituitary-adrenal (HPA) axis in type 2 diabetic patients, a condition preceded by pre-diabetes, has been shown to increase the risk of depression as well as cause downstream effects resulting in upregulation of gluconeogenesis and dyslipidemia. In addition, stress, either psychological from managing diabetes or lifestyle related, further activates the HPA axis causing an exaggerated stress response. This study investigated the activity of the HPA axis in selecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 75 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, when Mosili et al induced a chronic stress together with pre-diabetes, the rats were unable to mount a normal ACTH or GC response to subsequent acute stressor. further consolidating their observation of either impaired GC signalling or negative feedback [67]. Interestingly, diet would appear to affect the adrenal gland as increased GC secretion, adrenal cortical hyperplasia, and increased steroidogenesis have been reported in T2D-and obesity-inducing high fat diets [69].…”
Section: Glucocorticoids and Diabetesmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, when Mosili et al induced a chronic stress together with pre-diabetes, the rats were unable to mount a normal ACTH or GC response to subsequent acute stressor. further consolidating their observation of either impaired GC signalling or negative feedback [67]. Interestingly, diet would appear to affect the adrenal gland as increased GC secretion, adrenal cortical hyperplasia, and increased steroidogenesis have been reported in T2D-and obesity-inducing high fat diets [69].…”
Section: Glucocorticoids and Diabetesmentioning
confidence: 91%
“…Mechanistically, this passes through altered secretion of ACTH from the pituitary gland, leading to altered GC levels [65,66]. In a series of particularly well designed experiments, Mosili et al demonstrated that as rats entered a prolonged pre-diabetic state baseline ACTH levels under non-stressful conditions dropped, but GC levels were significantly elevated [67]. The HPA axis negative feedback loop should, under normal conditions bring down GC levels when ACTH levels are low [68] suggesting that the negative feedback is somehow impaired [65].…”
Section: Glucocorticoids and Diabetesmentioning
confidence: 99%
“…Chronic sleep issues elevate stress levels and trigger emotional disruptions such as anxiety and depression [20]. Stress-induced hyperactivity of the sympathetic nervous system and the hypothalamicpituitary-adrenal axis can lead to insulin resistance and glucose dysregulation [21]. The sympathetic nervous system is responsible for the body's "fight or flight" response, while the HPA axis is involved in regulating stress and other bodily functions [22].…”
Section: Mechanisms Underlying the Sleep-diabetes Linkmentioning
confidence: 99%
“…The sympathetic nervous system is responsible for the body's "fight or flight" response, while the HPA axis is involved in regulating stress and other bodily functions [22]. When these systems are hyperactive due to stress, they can influence the body's ability to properly respond to insulin, which is necessary for regulating blood sugar levels [21]. This phenomenon is known as insulin resistance, where the body's cells become less responsive to insulin's effects [21].…”
Section: Mechanisms Underlying the Sleep-diabetes Linkmentioning
confidence: 99%
See 1 more Smart Citation